2023
DOI: 10.1155/2023/6506244
|View full text |Cite
|
Sign up to set email alerts
|

Xuanhuang Runtong Tablets Relieve Slow Transit Constipation in Mice by Regulating TLR5/IL‐17A Signaling Mediated by Gut Microbes

Abstract: This study aims to investigate the regulation effects of Xuanhuang Runtong tablets (XHRTs) on intestinal microbes and inflammatory signal toll receptor 5 (TLR5)/interleukin-17A (IL-17A) in STC mice. First, high-performance liquid chromatography (HPLC) was used to verify the composition of XHRT and quality control. Then, the defecation ability of STC mice was evaluated by measuring fecal water content and intestinal transit function. The pathological examination of colonic mucosa was observed by Alcian Blue and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 48 publications
(53 reference statements)
0
2
0
Order By: Relevance
“…Decreased expression of CX43 might lead to weakened cell-to-cell communication, suggesting that the onset of constipation may be related to the destruction of the gap junction between cells. The expression of CX43 in the model group we studied was reduced, so it can be seen that CX43 as a channel changes, so that the electrophysiological signals of the colon cannot be produced, and also affect the signal transmission to the smooth muscle of the colon, which in turn leads to colonic motility disorders, which may be one of the important mechanisms causing constipation [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Decreased expression of CX43 might lead to weakened cell-to-cell communication, suggesting that the onset of constipation may be related to the destruction of the gap junction between cells. The expression of CX43 in the model group we studied was reduced, so it can be seen that CX43 as a channel changes, so that the electrophysiological signals of the colon cannot be produced, and also affect the signal transmission to the smooth muscle of the colon, which in turn leads to colonic motility disorders, which may be one of the important mechanisms causing constipation [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…AQPs represent important targets for traditional Chinese medicine in the treatment of digestive disorder including constipation ( Huang et al, 2022 ). A recent study showed that Xuanhuang Runtong tablets could reverse the disorder of AQP3 expression and thus relieve slow transit constipation in mice ( Liang et al, 2023 ). Moreover, the laxative effect of Daiokanzoto has been confirmed when used as a long-term treatment for chronic constipation probably by maintaining a persistent decrease of AQP3 expression and gut microbiota homeostasis ( Kon et al, 2018b ).…”
Section: Role Of Aqp3 In Constipation and Regulation Of Laxatives On ...mentioning
confidence: 99%